Proposal for the identification of residual stresses after turning and hardening of bearing steel - Šafář, Marek; Valíček, Jan; Harničárová, Marta; Šajgalík, Michal; Tozan, Hakan; Kušnerová, Milena; Drbúl, Mário; Kadnár, Milan; Czán, Andrej (Frontiers in Materials, 2023)
Residual stresses lead to undesirable unevenness of machined surfaces. It is empirically known that as cutting conditions increase, residual stresses increase, and surface roughness deteriorates. However, generally valid analytical relationships between these parameters alone cannot be directly identified, as they are multiparametric dependencies relating simultaneously to the elasticity and grain size of the material subjected to severe functional loading conditions. However, a fast and reliable prediction of the generation of residual stresses in metals subjected to severe processing can be provided by an accurate approximation. This publication presents an innovative approach to predict the residual stress state measured on 100Cr6 bearing steel after heat treatments, namely after quenching and tempering and after quenching, tempering, and turning. The residual stresses were measured by X-ray diffraction method, namely on a Proto iXRD diffractometer.